STRATEGI PENGEMBANGAN INDUSTRI KREATIF CAFE & RESTO DI KOTA PEKANBARU - Ahmad, Affandi; Azwar, Harahap; Ufira, Isbah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to analyze the right development strategy to be applied to the creative cafe & restaurant industry in Pekanbaru City. The population and sample used in this study were 72 cafes & restaurants. The analytical tool method used in this research is descriptive method and SWOT analysis in order to find out the constraints faced by the cafe & restaurant industry and provide appropriate alternative strategies for the cafe & restaurant industry in Pekanbaru. The results showed that the analytical methods used were EFAS matrix, IFAS matrix, and IE matrix. Based on the analysis of the external and internal environment of the cafe & restaurant industry in the city of Pekanbaru is in a position of growth where the strategy of concentration through horizontal integration. This means that the strategy adopted is more defensive, which is to avoid losing sales and losing profits so an SO strategy needs to be applied. In implementing the SO strategy, the cafe & restaurant industry in Pekanbaru City needs to prioritize the application of strategies to expand markets and improve product quality supported by technological developments, strategies to utilize strategic cafe & restaurant locations to make it easier for people to recognize products and be easily visited by the community, strategies utilize cheap prices and add menu variants to increase industrial activities so that the products offered are more varied and attract many visitors.Keywords: Cafe & Resto Industry, SWOT Analysis, IE Matrix